2015
DOI: 10.1155/2015/453826
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Synthetic Peptides Derived from Lactoferricin againstEscherichia coliATCC 25922 andEnterococcus faecalisATCC 29212

Abstract: Peptides derived from human and bovine lactoferricin were designed, synthesized, purified, and characterized using RP-HPLC and MALDI-TOF-MS. Specific changes in the sequences were designed as (i) the incorporation of unnatural amino acids in the sequence, the (ii) reduction or (iii) elongation of the peptide chain length, and (iv) synthesis of molecules with different number of branches containing the same sequence. For each peptide, the antibacterial activity against Escherichia coli ATCC 25922 and Enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
0
33
1
1
Order By: Relevance
“…Transgenesis has been suggested as a means to combat mastitis [ 28 ]. Recent studies have been used lactoferricin as anti-bacterial agent against diarrheal organisms ( S. aureus and E. coli ) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenesis has been suggested as a means to combat mastitis [ 28 ]. Recent studies have been used lactoferricin as anti-bacterial agent against diarrheal organisms ( S. aureus and E. coli ) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al [ 38 ], demonstrated the bovine lactoferricin antimicrobial activity assayed by agar diffusion test only. Lactoferricin was shown to interact with lipopolysaccharide (LPS) of the Gram-negative bacterial membrane of E. coli [ 39 ] hence it has high antibacterial activity against E. coli [ 40 ]. Our findings also showed the comparatively higher antibacterial property of bovine lactoferricin against E. coli in comparison to S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…We designed and synthesized three new cationic peptides based on the RRWQWR motif and prepared two other peptides for comparison (hy): LfcinB (20–25) (RRWQWR) and LfcinB (17–31) (FKCRRWQWRMKKLGA), the latter as reference peptide or antibacterial activity, based on results previously reported by Leon-Calvijo et al ( 2015 ). All peptides were synthesized on solid phase using the Fmoc/tBu methodology, as previously reported (Solarte et al, 2015 ; Huertas et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the dimeric peptide, di-FMOC-protected lysine was used, which enabled simultaneous synthesis of the two peptide chains (one from the α-amino group and the other, from the ε-amino group of this amino acid). The tetrameric peptide was obtained via oxidation of the dimeric peptide, (RRWQWR) 2 -K-Ahx-C, with 10% DMSO % in PBS buffer (pH 7.5), as described by Leon-Calvijo et al ( 2015 ), which led to formation of a disulfide bond between the side chains of the cysteine residues at the carboxyl terminus (Figure 1 ). All peptides were >90% pure (as determined by RP-HPLC) and had the expected molecular weight (determined by MALDI-TOF MS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation